2008
DOI: 10.1183/09031936.00095807
|View full text |Cite
|
Sign up to set email alerts
|

New evidence of risk factors for community-acquired pneumonia: a population-based study

Abstract: The aim of the present study was to identify risk factors for community-acquired pneumonia (CAP), with special emphasis on modifiable risk factors and those applicable to the general population.A population-based, case-control study was conducted, with a target population of 859,033 inhabitants aged .14 yrs. A total of 1,336 patients with confirmed CAP were matched to control subjects by age, sex and primary centre over 1 yr.In the univariate analysis, outstanding risk factors were passive smoking in never-smo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
316
2
12

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(354 citation statements)
references
References 30 publications
(37 reference statements)
24
316
2
12
Order By: Relevance
“…Findings from studies of the association between body mass index and acute respiratory infection are inconsistent, 6 but in general, studies powered to assess the effect of obesity on hospitalizations and/or mortality found increased risk associated with obesity 8 , 9 , 42 , 43 while studies examining the effect of obesity on healthcare service utilization for influenza‐like illness found no association or increased utilization associated with low BMI 4 , 44 , 45 , 46 . Thus, obesity may not be related to increased utilization of outpatient healthcare services for influenza‐like illness, but there is some evidence that obesity is related to increased rates of influenza‐related hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from studies of the association between body mass index and acute respiratory infection are inconsistent, 6 but in general, studies powered to assess the effect of obesity on hospitalizations and/or mortality found increased risk associated with obesity 8 , 9 , 42 , 43 while studies examining the effect of obesity on healthcare service utilization for influenza‐like illness found no association or increased utilization associated with low BMI 4 , 44 , 45 , 46 . Thus, obesity may not be related to increased utilization of outpatient healthcare services for influenza‐like illness, but there is some evidence that obesity is related to increased rates of influenza‐related hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza is considered ambulatory care sensitive as risk of influenza‐related hospitalizations, and severe outcomes may be mitigated through appropriate primary care 3 . Preventative efforts in the form of vaccination and the detection and control of chronic diseases, such as type II diabetes, can reduce rates of influenza‐related hospitalizations 4 , 5 . Despite these effective clinical interventions, the public health and economic impact of influenza epidemics remains high and motivates the need to identify additional individual‐ and community‐level risk factors that may respond to public health interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In the control group, 52.6% were males aged 58.9 ± 19.6 yrs and 47.4% were females aged 54.6 ± 20.6 yrs. Characteristics of both study groups have been previously published [19]. Main differences between cases and controls included smoking habit, alcohol intake (in men), BMI, educational level, and prevalence of diabetes, heart failure, chronic bronchitis, asthma or epilepsy.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the study methodology have been previously published [19]. The target population included 859,033 inhabitants older than 14 years of age assigned to any of the 64 participating primary care centres, selected according to their predisposition to take part in the study.…”
Section: Design and Study Populationmentioning
confidence: 99%
“…14,15 [Ib] Dose-response relationships with the current number of cigarettes smoked per day, pack-years of smoking, and time since quitting, have all been demonstrated in relation to invasive pneumococcal disease. 15,16 [III]…”
Section: Prevention and Vaccinationmentioning
confidence: 99%